Fluorescence of permitted lines in the orion nebula - Vladimir Escalante (Revista Mexicana de Astronomía y Astrofísica, 2002)
The predicted emission spectrum of N II has been compared with recent observations of permitted emissionlines in the Orion nebula. Fits of nebular models to the data show qualitative agreement with an spectrumexcited by uorescence of starlight absorption, but there are large quantitative discrepancies with the observedintensities in many cases.